Implementation of Lean Management Activities Based on Project Management and Lean Production for Improving the Efficiency of the Enterprises - Anna DOLINSKAIA; Aleksandr KOROLENKO; Natalya DZENZELIUK; Anastasiya KAMALOVA; Leonid BAEV (Communications of International Proceedings, 2021)
Modern organizations face different challenges in today uncertain world. These challenges can be different: competition within industry, technological development and improvement, growing customer expectations, quality and time demands, governmental regulations. One of the effective ways to meet these challenges is to have effective management which has increasing productivity among its priorities. The main task of this article is to present results for determine the lean management, a complex of combined principles, instruments and methodology of lean manufacturing and project management.
Keywords: lean management; lean production; project management; efficiency; productivity; production cycle; projects.